Polyrotaxane-based supramolecular theranostics - Yu, Guocan (Nat Commun, 2018)
The development of smart theranostic systems with favourable biocompatibility, high loading efficiency, excellent circulation stability, potent anti-tumour activity, and multimodal diagnostic functionalities is of importance for future clinical application. The premature burst release and poor degradation kinetics indicative of polymer-based nanomedicines remain the major obstacles for clinical translation. Herein we prepare theranostic shell-crosslinked nanoparticles (SCNPs) using a β-cyclodextrin-based polyrotaxane (PDI-PCL-b-PEG-RGD⊃β-CD-NH(2)) to avoid premature drug leakage and achieve precisely controllable release, enhancing the maximum tolerated dose of the supramolecular nanomedicines. cRGDfK and perylene diimide are chosen as the stoppers of PDI-PCL-b-PEG-RGD⊃β-CD-NH(2), endowing the resultant SCNPs with excellent integrin targeting ability, photothermal effect, and photoacoustic capability. In vivo anti-tumour studies demonstrate that drug-loaded SCNPs completely eliminate the subcutaneous tumours without recurrence after a single-dose injection combining chemotherapy and photothermal therapy. These supramolecular nanomedicines also exhibit excellent anti-tumour performance against orthotopic breast cancer and prevent lung metastasis with negligible systemic toxicity.